Phylogenomic analysis and molecular identification of true fruit flies - He, Rong; Wang, Shuping; Li, Qiang; Wang, Zuoqi; Mei, Yang; Li, Fei (Frontiers in Genetics, 2024)
The family Tephritidae in the order Diptera, known as true fruit flies, are agriculturally important insect pests. However, the phylogenetic relationships of true fruit flies, remain controversial. Moreover, rapid identification of important invasive true fruit flies is essential for plant quarantine but is still challenging. To this end, we sequenced the genome of 16 true fruit fly species at coverage of 47 -228 ×. Together with the previously reported genomes of nine species, we reconstructed phylogenetic trees of the Tephritidae using benchmarking universal single-copy ortholog (BUSCO), ultraconserved element (UCE) and anchored hybrid enrichment (AHE) gene sets, respectively. The resulting trees of 50% taxon-occupancy dataset for each marker type were generally congruent at 88% nodes for both concatenation and coalescent analyses. At the subfamily level, both Dacinae and Trypetinae are monophyletic. At the species level, B. dorsalis is more closely related to B. latifrons than B. tryoni. This is inconsistent with previous conclusions based on mitochondrial genes but consistent with recent studies based on nuclear data. By analyzing these genome data, we screened ten pairs of species-specific primers for molecular identification of ten invasive fruit flies, which PCR validated. In summary, our work provides draft genome data of 16 true fruit fly species, addressing the long-standing taxonomic controversies and providing species-specific primers for molecular identification of invasive fruit flies.